Finding fishers: determining fisher occupancy in the Northern Rocky Mountains. Issue 2 (11th January 2022) - Krohner, Jessica M.; Lukacs, Paul M.; Inman, Robert; Sauder, Joel D.; Gude, Justin A.; Mosby, Cory; Coltrane, Jessica A.; Mowry, Rebecca A.; Millspaugh, Joshua J.
Abstract: Monitoring rare and elusive carnivores is inherently challenging because they often occur at low densities and require more resources to effectively assess status and trend. The fisher ( Pekania pennanti ) is an elusive mesocarnivore endemic to North America; in its western populations it is classified as a species of greatest conservation need. During winter of 2018–2019, we deployed remotely triggered cameras in randomly selected, spatially balanced 7.5‐km × 7.5‐km grid cells across a broad study area in western Montana, Idaho, and eastern Washington, USA. As part of this large‐scale, multi‐state monitoring effort, we conducted an occupancy assessment of the Northern Rocky Mountain fisher population at a range‐wide scale. We used non‐spatial occupancy models to determine the current extent of fisher occurrence in the Northern Rocky Mountains and to provide baseline occupancy estimates across a broad study area and a refined sampling frame for future monitoring. We used a spatial occupancy model to determine patterns in fisher occurrence across their Northern Rocky Mountain range while explicitly correcting for spatially induced overdispersion. Additionally, we assessed factors that influenced fisher occurrence through covariate occupancy modeling that considered predicted fisher habitat, site‐level environmental characteristics, and the influence of available harvest records (incidental and regulated). We detected fishers in 32 out of 318 (10%) of our surveyed cells, and estimated that overall, 160 (14%; 95% CI = 115–218) of 1, 143 grid cells were occupied by fishers. Fisher occupancy was positively associated with our stratum that contained cells with a greater proportion of predicted fisher habitat and with proximity to nearest 2000–2015 harvest location. Fisher occupancy was weakly and positively associated with increased canopy cover. Our spatial model identified 2 areas with higher predicted occupancy: a large area across the Idaho Nez Perce‐Clearwater National Forest, and a smaller area in the Cabinet Mountain Range crossing the northern border of Idaho and Montana. We used spatial occupancy results from our original sampling frame to create a biologically derived refined sampling frame for future monitoring. Within the bounds of our refined sampling frame, we estimated that 155 (22%; 95% CI = 110–209) of 700 grid cells were occupied by fishers. By incorporating our increasing understanding of fisher habitat with contemporary analytical techniques, we defined current range‐wide occupancy of the Northern Rocky Mountain fisher population, identified core areas of fisher occurrence for future conservation efforts, and used our model results to create a refined sampling frame for future fisher monitoring in the Northern Rocky Mountains. Abstract : We provide occupancy and detection probability data from the first multi‐state, range‐wide study of the Northern Rocky Mountain fisher population. We provide baseline data for comparison against future fisher surveys as well as a study design and protocol to conduct future surveys.